ANALISIS KEMAMPUAN PENALARAN ANALOGI SISWA BERDASARKAN TIPE KEPRIBADIAN MBTI (MAYERS-BRIGGS TYPE INDICATOR) DALAM MENYELESAIKAN SOAL HUBUNGAN GRADIEN PADA SISWA KELAS VIII SMP NEGERI 16 SAROLANGUN - Risma Siamamora; Dewi Prapita; Fitriani Silvia (Universitas Batanghari Jambi, 2017)
This research is motivated by VIII Grade Students of SMP N 16 Sarolangun who can not use their analogical reasoning to determine gradient relationship with straight line equation in learning process. This research includes descriptive qualitative research type by using analysis to know the analogy reasoning ability of MBTI personality type student (Mayers-Briggs Type Indicator) in solving the problem of gradient relationship and straight line equation. the subjects in this study were students of MBTI personality type (Mayers-Briggs Type Indicator) in Grade VIII SMP Negeri 16 Sarolangun 2015/2016 academic year, amounting to 52 students. Data collection method used in this research is questionnaire method, analogy reasoning and interviewing test. Required data obtained through questionnaires, analogous reasoning tests, and interview guides that have been tested first through validator opinion test. The results of this study can be concluded that the analogy reasoning abilities in grade VIII students of SMP Negeri 16 Sarolangun have 12 students of ESTJ personality type of 24% including moderate analogy reasoning group, 28 students ESFJ type of personality of 56% including low analogy reasoning group, while 10 ISFJ personality type students by 20% including low analogy reasoning abilities.Keywords: Kemampuan Penalaran Analogi, Tipe Kepribadian MBTI (Mayers-Briggs Type Indicator), Hubungan Gradien dengan Persamaan Garis Lurus